Impact of Spatial Contamination Levels of Heavy Metals on Cowpea and Soybean Growth, Yield and Nodulation - Amarachi Nwokocha; Sani Idris; Mercy Zakka; Olufunso Akinboye; Oluwafunmike Oyekale; Olajire Fagbola (مجلة ديالى للعلوم الزراعية)
Agricultural soil contamination poses a global threat to crop productivity and food safety. Agricultural expansion led farmers to cultivate cowpea (Vigna unguiculata) and soybean (Glycine max) on land near a wet battery waste disposal site. This study evaluates the effect of battery waste deposits at varying distances on biomass, grain yields, and nodulation of these crops, as well as the impact on microbial populations. Twenty (20) soil sampling points were randomly selected across four sites: a non-contaminated control site, the main battery dumpsite (MDS), and areas located 20 meters and 40 meters away from the MDS, with five sampling points per site. Using a 2 × 4 factorial Complete Randomized Design, the crops were grown with recommended best practices and inoculated with effective USDA 110 Bradyrhizobium strains. Results from analyses indicated that contamination significantly reduced plant height, leaf number, pod number, dry root and shoot weights, grain yield, and microbial population. Soil analysis revealed high concentrations of Lead (Pb), Chromium (Cr), Arsenic (As), and Cobalt (Co) at the contamination sites. Specifically, Pb levels were 1772.4, 563.1, and 157.6 times higher in the MDS, 20 MDS, and 40 MDS sites, respectively, compared to the control soil, which had a concentration of 20.10 mg kg–1. The bacterial population decreased by approximately 83% in the MDS area relative to the control. Findings from this study indicate that wet battery waste deposition significantly increases soil contamination with heavy metals, adversely affecting legume yield, growth, and microbial populations, rendering the area unsuitable for cultivation